PPT1 Reduction Contributes to Erianin-Induced Growth Inhibition in Oral Squamous Carcinoma Cells - Luo, Qingqiong; Li, Xiaoyan; Gan, Guifang; Yang, Meng; Chen, Xu; Chen, Fuxiang (Frontiers in Cell and Developmental Biology, 2021)
The anticancer properties of erianin have been recently discovered. However, the antitumor effect of erianin in oral squamous cell carcinoma (OSCC) remains unclear. In this study, we demonstrated that erianin can hamper OSCC cells growth both in vitro and in vivo. Erianin induced obvious G2/M arrest as well as apoptosis and gasdermin E (GSDME)-dependent pyroptosis in OSCC cells. Moreover, erianin increased autophagosome formation but decreased autolysosome function. Further study indicated that erianin significantly suppressed the expression of protein-palmitoyl thioesterase 1 (PPT1) and mTOR signaling. PPT1 has been reported to be a critical regulator of cancer progression by its modulation of autophagy and mTOR signaling. According to online databases, higher expression of PPT1 has been observed in OSCC tissues and is associated with poorer patient prognosis. As overexpression of PPT1 significantly reversed erianin-induced growth inhibition in OSCC cells, we identified the importance of PPT1 reduction in erianin-induced growth suppression. With the xenograft model, we confirmed the antitumor effect of erianin in vivo. Erianin efficiently decreased the tumor sizes, together with visibly reduced expression of PPT1 and phosphorylation of mTOR in the xenograft tumor tissues. Therefore, the present study indicated that erianin may be potentially used in OSCC therapy.